The Study of Thermal Energy Storage for Thermal Comfort Building - Fitri, Ahmad (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Buildings used 1/3 global primary energy and the shortage of electricity supply become main concern to the society. To fulfill the demand of the electricity, thermal energy storage is required to supply electricity. The main research of this project is fulfilling the demand of electricity and can explain the importance of thermal energy storage to the community. This study aims to identify the amount of electrical energy can be generated by the thermal energy storage. This study is carried out by identifying the power flow of electricity, energy consumption and the demand of electricity for a certain place and the place that has been taken for this project is Sandakan, Sabah. From the result, it is observed that the demand of electricity is increasing by year because of the increasing of population and by the year of 2018 the shortage of electricity is 60.4 MW. Therefore, the suggestion of construction sensible thermal energy storage using water as medium to supply electricity to Sandakan area is necessary for it. With these proposed measure, thermal energy storage estimated can reduce the shortage of electricity by 8% and supply more electricity per year respectively.